2002
DOI: 10.1152/jn.00472.2001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Reward Expectation on Visuospatial Processing in Macaque Lateral Prefrontal Cortex

Abstract: The lateral prefrontal cortex (LPFC) has been implicated in visuospatial processing, especially when it is required to hold spatial information during a delay period. It has also been reported that the LPFC receives information about expected reward outcome. However, the interaction between visuospatial processing and reward processing is still unclear because the two types of processing could not be dissociated in conventional delayed response tasks. To examine this, we used a memory-guided saccade task with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
142
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(159 citation statements)
references
References 52 publications
16
142
0
1
Order By: Relevance
“…In fact, the level of expectations is similar in the DR task and in repetition, and differs in the search period. Variation in the size of the reward expected by the monkey does not induce delay activity variations comparable with those observed depending on types of trials, a result that have been observed for planning related activity (Kobayashi et al, 2002;Amemori and Sawaguchi, 2006). Finally, pure expectation (directly related to reward probability) does not account for activity changes be- tween the last trials in the search period (indices 3) and the other correct trials: if the amplitude of activity were related to reward probability, then activity should remain elevated for the following repetition trials during which reward expectation is maximal (i.e., during which the probability to get a reward is p ϭ 1).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In fact, the level of expectations is similar in the DR task and in repetition, and differs in the search period. Variation in the size of the reward expected by the monkey does not induce delay activity variations comparable with those observed depending on types of trials, a result that have been observed for planning related activity (Kobayashi et al, 2002;Amemori and Sawaguchi, 2006). Finally, pure expectation (directly related to reward probability) does not account for activity changes be- tween the last trials in the search period (indices 3) and the other correct trials: if the amplitude of activity were related to reward probability, then activity should remain elevated for the following repetition trials during which reward expectation is maximal (i.e., during which the probability to get a reward is p ϭ 1).…”
Section: Discussionsupporting
confidence: 68%
“…Thus, modulation of prefrontal activity during the PS task does not simply reflect an anticipatory reward-related bias as reported in the caudate nucleus . However, it is possible that DLPFC integrates some dimensions of reward expectation (Kobayashi et al, 2002;Amemori and Sawaguchi, 2006) with other factors involved in learning and control of behavior. One candidate is uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…The FT neurons may receive the signals of reward prediction from the orbitofrontal cortex (OFC) (Tremblay and Schultz, 1999;Hikosaka and Watanabe, 2000;Roesch and Olson, 2004;Simmons and Richmond, 2008), prefrontal cortex (Leon and Shadlen, 1999;Kobayashi et al, 2002a;Roesch and Olson, 2003), or the striatum (Mena-Segovia et al, 2004;Hikosaka et al, 2006;Winn, 2006). These structures may learn the cue-reward magnitude contingency during the training and task periods as a synaptic memory and recall that memory as the signals of the predicted reward magnitude at the time of cue presentation.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, it projects to dorsolateral prefrontal and premotor regions, and could, thus, influence behavioral output (51,54). Neurophysiological studies have shown that single lateral prefrontal neurons use reward information to increase spatial discrimination, encode reward-based stimulus category, and integrate reward and response history (64)(65)(66). Together, these findings on expected reward value and risk processing in the lateral prefrontal cortex underline the role of this structure as a key component of the decision system of the brain.…”
Section: Individual Differences In Risk Processingmentioning
confidence: 94%